دراسة تأثير توزيع القضبان الكربونية CFRP في مقاطع الجوائز البيتونية المسلحة بشكل هجين على سلوكها الإنعطافي - جحجاح, غاندي علي; عبود, أحمد علي; حشمة, ميرفت حسن (Latakia University Journal -Engineering Sciences Series, 2014)
إن الاستخدام المشترك لقضبان فولاذية وكربونية في تسليح الجوائز البيتونية يؤدي إلى الحصول على جوائز ذات سلوك يختلف عن سلوك الجوائز المسلحة بالفولاذ فقط. يتعرض هذا البحث لحالة تسليح الجوائز بطبقتين من القضبان والمتغيرات الأساسية هي نسبة التسليح وتوزيع القضبان الكربونية في المقطع العرضي. تم اختبار أربع مجموعات مكونة من 12 جائزاً، كل منها مسلح بأربعة قضبان متوضعة على طبقتين، وتضم المجموعة الأولى ثلاثة جوائز معيارية مسلحة بقضبان فولاذية, أما المجموعة الثانية فتضم ثلاثة جوائز مسلحة بقضبان كربونية. وتضم كل من المجموعتين الثالثة والرابعة ثلاثة جوائز مسلحة بقضيبي فولاذ وقضيبي كربون، حيث في المجموعة الثالثة تتوضع القضبان الفولاذية في الطبقة العلوية والكربونية في الطبقة السفلية، وفي المجموعة الرابعة تتوضع القضبان الفولاذية في الطبقة السفلية والكربونية في الطبقة العلوية. حصلت في جوائز المجموعة الثانية المسلحة بقضبان كربونية قيم أكبر للسهوم وزادت قدرة التحمل بالمقارنة مع الجوائز الأخرى, وكان لجوائز المجموعتين الثالثة والرابعة تقريباً نفس قدرة التحمل الأعظمية وتماثلت في سلوكها حتى مستوى تحميل يساوي تقريباً 75% من قدرة تحملها وبعد ذلك زادت التشوهات في المجموعة الرابعة مقارنة مع المجموعة الثالثة حتى الانهيار. The mixed use of steel bars and carbon rods in concrete beams can offer beams with different behaviour from that of steel reinforcement only. This paper studies the case of reinforcing concrete beams with two layers of bars, and the main parameters investigated are the proportion and the distribution of carbon rods in the cross-section. Four groups containing 12 beams are tested, and each is reinforced with 4 bars located in two layers. The first group includes three control beams reinforced with steel bars, while the second includes three beams reinforced with carbon bars. Each of the third and fourth groups includes three beams reinforced with two steel bars and two carbon bars, whereas in the third group, steel bars are located above carbon ones, but in the fourth group, steel bars are located under carbon ones. Concrete beams reinforced with carbon rods in the second group exhibit a higher load carrying capacity and deflections, compared with other beams. However, the beams in the third and fourth groups have approximately the same load carrying capacity and the same behaviour up to the load level equal to 75% of their load carrying capacity. But after that, the beams in the fourth group become more deformed, compared with those of the third group.